Early Intervention Service Delivery via Telehealth During COVID-19: A Research-Practice Partnership - Jessica Kronberg; Elaine Tierney; Anna Wallisch; Lauren M. Little (International Journal of Telerehabilitation)
Coaching has been identified as a best practice for early intervention (EI) services provided through the Individuals with Disabilities Education Act (IDEA) Part C. The current study describes the establishment and progress of a research-relationship partnership to deliver coaching via telehealth during the COVID-19 pandemic. Community-based EI providers implemented 9-weeks of telehealth coaching and evaluated the extent to which child and caregiver outcomes differed between families that had previously received in-person services versus telehealth only. Four EI providers completed the intervention with n=17 families of children aged 6-34 months during the pandemic (April-August 2020). We used the Canadian Occupational Performance Measure (COPM) and Goal Attainment Scaling (GAS) to collect outcomes on caregiver identified goals; we used Wilcoxon Signed Rank Tests to examine pre- to post-intervention data. Results showed significant improvements in parent satisfaction, child performance, and goal attainment (all p<.01). Findings suggest that telehealth coaching procedures implemented by community-based EI providers resulted in improvements in caregiver identified goals for young children.